Groundwater flow modelling of main groundwater reservoirs in the Gdańsk region, Poland - Kordalski, Zbigniew; Sadurski, Andrzej (Geologos, 2018)
During the last nine years, the 133 main groundwater reservoirs in Poland (MGR) have been documented; these were published last year. Some of these are situated in the coastal zone of the southern Baltic Sea. MGR numbers 111 and 112 are in the Gdańsk area and are discussed in the present paper. The study area is situated on the border region of the moraine plateau of the Cashubian Lakeland, the western part of the Vistula River delta plain and the Bay of Gdańsk. The area of the main groundwater reservoir in no. 112 is developed in Quaternary strata and referred to as Żuławy Gdańskie; it comprises predominantly the city of Gdańsk and slightly exceeds 100 km2. There is also a Cretaceous aquifer, rich in groundwater resources, which is named MGR no. 111, beneath the Quaternary reservoir mentioned above. The area studied and modelled totalled 364 km2, on account of the hydraulic connection between these aquifers. Methods of hydrogeological research, groundwater flow simulations, resources calculation are outlined in the present paper.